Association Between High Serum Anion Gap and All-Cause Mortality in Non-Traumatic Subarachnoid Hemorrhage: A Retrospective Analysis of the MIMIC-IV Database - Zhong, Changli; Ye, Min; Hu, Liyi; Liu, Jiuling (Frontiers in Neurology, 2022)
Abstract Background: High serum anion gap (AG) on admission is often correlated with poor outcomes in critically ill patients; however, data in patients with non-traumatic subarachnoid hemorrhage (SAH) are lacking. Herein, we aimed to identify the association between serum AG and all-cause mortality in patients with non-traumatic SAH. Methods: A retrospective analysis of data from the Medical Information Mart for Intensive Care (MIMIC-IV) database was performed in critically ill patients with non-traumatic SAH. Serum AG was collected on Intensive Care Unit (ICU) admission, and ICU and hospital all-cause mortality were analyzed. The multivariate Cox proportional hazard regression model and Kaplan-Meier survival curve analysis was used to analyze the correlation of serum AG with ICU and hospital all-cause mortality. Furthermore, interaction and subgroup analyses were evaluated for the consistency of these correlations. Results: A total of 893 patients with non-traumatic SAH were included in this study. The all-cause mortality of ICU and hospital were 14.8% (132/893) and 18.9% (169/893), respectively. Multivariate analysis after adjusting for potential confounders indicated that high serum AG level ( ≥ 16mmol/L) were associated with increased risk of ICU and hospital all-cause mortality as compared to that with low serum AG level ( <16 mmol/L), (hazards ratio (HR): 2.31 [95% confidence interval (CI): 1.58-3.38]) and HR: 1.91 [95% CI: 1.36-2.67)], respectively). Similarly, the Kaplan–Meier (K-M) survival curve also showed that patients with high serum AG level presented with a lower survival rate. Stratified analyses further showed that depending on the variables testes, an association between higher serum AG level and hospital all-cause mortality in different subgroups was observed. Conclusion: Among patients with non-traumatic SAH, high serum AG level at ICU admission was associated with increased ICU and hospital all-cause mortality.